2007
DOI: 10.1063/1.2741542
|View full text |Cite
|
Sign up to set email alerts
|

Zero electron kinetic energy spectroscopy of the para-fluorotoluene cation

Abstract: Zero electron kinetic energy (ZEKE) spectroscopy is employed to gain information on the vibrational energy levels of the para-fluorotoluene (pFT) cation. Vibrationally resolved spectra are obtained following excitation through a range of intermediate vibrational energy levels in the S1 state. These spectra allow the observation of different cationic vibrational modes, whose assignment is achieved both from a knowledge of the S1 vibrational states and also by comparison with density functional calculations. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
77
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 33 publications
(95 citation statements)
references
References 24 publications
(50 reference statements)
18
77
0
Order By: Relevance
“…In the present experiments, it was confirmed that the photoionization cross-section for toluene was about an order of magnitude lower than that of the para-fluorotoluene (pFT) molecule we have studied previously; 47 this is in line with conclusions reached by Bacon and Hollas 48 with regard to the oscillator strength of the S 1 ← S 0 transition for toluene compared to other monosubstituted benzenes. As such, there was a continual compromise between resolution and signal-to-noise ratios in the ZEKE spectra and this limited the range of S 1 resonances we could employ as intermediates.…”
Section: Methodssupporting
confidence: 93%
See 1 more Smart Citation
“…In the present experiments, it was confirmed that the photoionization cross-section for toluene was about an order of magnitude lower than that of the para-fluorotoluene (pFT) molecule we have studied previously; 47 this is in line with conclusions reached by Bacon and Hollas 48 with regard to the oscillator strength of the S 1 ← S 0 transition for toluene compared to other monosubstituted benzenes. As such, there was a continual compromise between resolution and signal-to-noise ratios in the ZEKE spectra and this limited the range of S 1 resonances we could employ as intermediates.…”
Section: Methodssupporting
confidence: 93%
“…The excitation laser has been calibrated by comparison of the bands observed in the (1 + 1) REMPI spectrum in the present work and the fluorescence excitation spectrum reported by Hickman et al, 3 with the origin position calibrated to that reported by Borst and Pratt; 31 use was also made of the known positions of the S 1 origin of pFT, 47 observed in a recent series of experiments with an absolute error of ±1 cm −1 ; we estimate our relative error to be ∼0.5 cm -1 . Calibration of the ionization laser has been performed through comparison of the ZEKE bands observed in the present work and those seen for toluene by Lu et al 42 …”
Section: Methodsmentioning
confidence: 94%
“…At 441 cm -1 is the intense, symmetryallowed D11 ZEKE band and combination band with this vibration are also present in most spectra. The assignments of these higher-wavenumber features are largely the same as in our previous publication, 37 albeit with a different nomenclature; we shall address this higherwavenumber region in more detail in a future publication. 55…”
Section: A Rempi Spectrummentioning
confidence: 89%
“…The recorded spectrum is very similar to that reported by us in ref. 37, and so we only show a vertically-expanded view of the lowwavenumber region of the new spectrum in Figure 3, with an expanded view of the first 150 cm -1 presented in Figure 4(b). All ZEKE spectra have been calibrated to an adiabatic ionization energy of 70946 cm -1 corresponding to the origin transition, in line with our earlier value.…”
Section: A Rempi Spectrummentioning
confidence: 99%
See 1 more Smart Citation